Effect of preharvest conditions on cut-flower quality - Verdonk, Julian C.; van Ieperen, Wim; Carvalho, Dália R. A.; van Geest, Geert; Schouten, Rob E. (Frontiers in Plant Science, 2023)
see manuscript